Failure of Value Co-creation; Co-destruction of Brand Value in Social Media - Ghazale Taheri; Azim Zarei; Davood Feiz; Mehdi Dehghani soltani (‫مدیریت بازرگانی)
Objective With the increase in the use of social media platforms by customers to buy products and services of brands, the importance of interactions between companies and customers to improve the value of brands has increased. Therefore, brand managers have changed their interactions with customers from transaction-based cooperation to relationship-based cooperation. They have realized that just as customers can co-create brand value during design, production, and marketing, conversely, they can destroy the value of brands if their interests are neglected, and their well-being is compromised. Therefore, it is necessary to prevent this phenomenon by knowing the driving forces in the co-destruction of brand value. The present study aims to identify the most effective factors contributing to the co-destruction of brand value in social media.